Can Small Medium Industries (SMI) In Developing Countries Survive In Uncertain Situations? : Applying The Concept Of Sustainable Entrepreneurship As A Solution - nabil, abil; nabil, abil (Archives of Business Research, 2019)
The hegemony of the manufacturing sector has become an inherent identity for the majority of developing countries in the Asian continent. This sector has massively managed to provide employment for informal workers who are not provided with special skills. If classified by business scale, the small and medium industries (SMIs) segment is worthy of calculating its contribution. SMIs is a fundamental component in regional economic aspects, including in Indonesia. The increasingly competitive climate of business competition has prompted the SMIs to adopt certain patterns that play a role in maintaining business existence in the future. Sustainable entrepreneurship is introduced as a concept that offers options for these challenges. Based on empirical research it is known that the process of implementing Sustainable Entrepreneurship in the realm of SMIs has a positive relationship with the concept of business model innovation and entrepreneurial bricolage. This finding is an objective reason for researchers to raise research topics that focus on IKM. The data collected came from 39 respondents who were status as IKM owners with Dolls products in Bandung City. This research was conducted through a quantitative approach. The analytical method used in this study is multiple regression analysis which is used to test the influence of variables. The results of data processing show that business models of innovation and entrepreneurial bricolage have a significant influence on sustainable